Plasma as a tool for enhancing insulation properties of polymer composites1. Issue 47 (27th May 2015) - Puliyalil, H.; Cvelbar, U.; Filipič, G.; Petrič, A. D.; Zaplotnik, R.; Recek, N.; Mozetič, M.; Thomas, S.
<x xml:space="preserve">Abstract</x> A novel method for improving the CTI performance level of polyphenol composites by oxygen plasma selective etching.